Financial Screening Pada Saham Syariah Di Tinjau Dari Aspek Maslahah Mursalah - Andre Zanij Deananda (Jurnal Ilmiah Kutei, 2025)
Sharia shares are an adaptation of the conventional stock market that was first introduced in Indonesia. The difference between Sharia shares and conventional stocks lies in the screening method found in Sharia stocks, especially in the financial screening method. However, there is a problem with the financial screening method where interest-based debt and non-halal income are still allowed with certain limitations on Sharia stock instruments. The provision of these limitations is given by the OJK by referring to the DSN-MUI Fatwa. Maslahah mursalah is one method that can see the reasons for allowing the issuance of limits on interest-based debt and non-halal income on sharia stock instruments. This research will be a type of notary public legal research. The data used is secondary data where the researcher will use data sources in the form of books, journals, articles, and regulations related to this research. The results of this study are to see the aspects that must be considered in the maslahah mursalah method as one method that can be used in exploring the law and see the reasons for providing financial screening limitations on sharia shares in terms of maslahah mursalah.